Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.jsps.2020.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanofiber alignment on the release of a water-soluble drug from cellulose acetate nanofibers

Abstract: Cellulose acetate nanofibers with different degrees of alignment (randomly aligned (RA), partially aligned (PA), and highly aligned (HA)) were produced using an electrospinning technique. The different degrees of alignment were obtained by adjusting the rotation speed of the collector. Alpha-arbutin (3% w/w) employed as a model water-soluble compound was incorporated into the nanofibers during the fabrication process. The drug release characteristics were investigated using the nanofiber mats with the same siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…[13] Thus, morphology plays a key role in drug release kinetics, since, besides fiber influence, higher porosity and loading contributes to faster release, and the beads on nanofibers may act as drug reservoirs. [6,18,41,[43][44][45][46][47][48] Also, if there is an uneven drug distribution in the solution, or the drug is located around the nanofiber surface, defects, and initial burst release of the drug followed by diffusion may be observed. [6,13] In general, biodegradable or swellable polymers are employed in nanofibers form as drug carriers, [7] and natural hydrophilic polymers exhibit better biocompatibility and low immunogenicity making them appropriate candidates for biological applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[13] Thus, morphology plays a key role in drug release kinetics, since, besides fiber influence, higher porosity and loading contributes to faster release, and the beads on nanofibers may act as drug reservoirs. [6,18,41,[43][44][45][46][47][48] Also, if there is an uneven drug distribution in the solution, or the drug is located around the nanofiber surface, defects, and initial burst release of the drug followed by diffusion may be observed. [6,13] In general, biodegradable or swellable polymers are employed in nanofibers form as drug carriers, [7] and natural hydrophilic polymers exhibit better biocompatibility and low immunogenicity making them appropriate candidates for biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent publications about electrospun CA nanofibers have demonstrated the drug sustained-release profiles in different manners such as trilayer nanofibers, [56] drug depots, [41,57] and by micropatterned induced surface hydrophobicity. [58] The faster release profile of Alpha-arbutin (hydrophilic drug) was achieved with highly aligned CA nanofibers by Patrojanasophon et al [47] According to the authors, the organized arrangement along with the lower degree of entanglements facilitated the drug diffusion from the nanofibers. [47] A tunable sustained release of ibuprofen studied by Yang et al [59] was attributed to the presence of CA coating, which was responsible to eradicate initial burst release.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the entrapment efficiency of metronidazole in the nanofiber mats was 82–99% and at least 30% of metronidazole was released in the initial period followed by a sustained-release for up to 7 days. To further prolong the sustained release of loaded pharmaceuticals in the PLGA mats, a higher drug loading, a greater polymer-to-drug ratio, a polymer of higher molecular weight [ 37 ], and/or a highly aligned fiber structure [ 38 ] may be adopted. On the other hand, owing to the shielding influence of the shell PLGA layer, the initial burst of CTGF from the sheath-core-structured nanofibers was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has some drawbacks that include poor thermal stability, weak chemical resistance, and inferior mechanical performance. Hence, the polysaccharide is modified with nanoparticle, [18] other polymers, [19,20] and fibres, [21] to improve their application potentialities. Some of the modified cellulose acetate were studied for their antimicrobial activity, [22,23] heavy metal extraction, [24,25] drug delivery, [26] tissue engineering, [27] wound dressing, [28] water treatment technology, [29] waterborne coating, [30] and antifouling coating [30,31] .…”
Section: Introductionmentioning
confidence: 99%